2008
DOI: 10.1007/s11258-008-9544-5
|View full text |Cite
|
Sign up to set email alerts
|

Growth, biomass allocation, morphology, and photosynthesis of invasive Eupatorium adenophorum and its native congeners grown at four irradiances

Abstract: Eupatorium adenophorum is one of the more noxious invasive plants worldwide. However, the mechanisms underlying its invasiveness are still not well elucidated. In this study, we compared the invader with its two native congeners (E. heterophyllum and E. japonicum) at four irradiances in terms of growth, biomass allocation, morphology, and photosynthesis. The higher light-saturated photosynthetic rate (P max ) and total leaf area of the invader may contribute to its higher relative growth rate (RGR) and total b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
73
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(78 citation statements)
references
References 34 publications
4
73
0
1
Order By: Relevance
“…In a previous study on a wider set of Australian acacias, we also found that species native to moister and cooler regions have more chances of becoming invasive elsewhere (Castro-Díez et al 2011). Species evolved under low climatic stress have more chances to be selected for fast growth (Grime 1988) a feature frequently associated with invasiveness (Burns 2004; Grotkopp and Rejmánek 2007;Leishman et al 2007;Zheng et al 2009). An alternative explanation for this pattern may be Number of uses Abundance (b) (a) Fig.…”
Section: \0001supporting
confidence: 59%
“…In a previous study on a wider set of Australian acacias, we also found that species native to moister and cooler regions have more chances of becoming invasive elsewhere (Castro-Díez et al 2011). Species evolved under low climatic stress have more chances to be selected for fast growth (Grime 1988) a feature frequently associated with invasiveness (Burns 2004; Grotkopp and Rejmánek 2007;Leishman et al 2007;Zheng et al 2009). An alternative explanation for this pattern may be Number of uses Abundance (b) (a) Fig.…”
Section: \0001supporting
confidence: 59%
“…It is now widely distributed in Yunnan, Guizhou, Sichuan, Guangxi, and Xizang (Wei et al, 2011). Due to the fast spreading, the weed has caused significant damage to the ecological environment, economic development, and human health (Zheng et al, 2009). Chemical control of E. adenophorum was effective using herbicides such as glyphosate aqueous solution (Zhang et al, 2005), sulfometuron-methyl soluble powder (Huang et al, 2001), and picloram (Cao et al, 2006;Li et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Although it is seldom found that an invasive species outperforms native species under all conditions (ZHENG et al, 2009), increasing resource availability often facilitates alien plant invasions (DAEHLER, 2003). Therefore, environmental conditions should be considered when identifying the traits contributing to invasiveness.…”
Section: Discussionmentioning
confidence: 99%